Find the sum of all real satisfying the above statement.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y = 3 1 + x . Thus, 1 + 2 + x = 3 1 + x ⟹ 1 + 1 + y 3 = y .
This implies y 2 − 1 = 1 + y 3 , so y 4 − 2 y 2 + 1 = 1 + y 3 . This simplifies to y 4 − y 3 − 2 y 2 = 0 , which simplifies to y 2 ( y + 1 ) ( y − 2 ) = 0 .
Therefore, y = 0 , − 1 , 2 . Testing, we find only y = 2 works, which implies x = 4 9 is the only solution.
Therefore, the sum of all real x satisfying 1 + 2 + x = 3 1 + x is 4 9 .